EBOOK BERBASIS KETERAMPILAN BERPIKIR KRITIS - Hendra Nelva Saputra (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2019)
Ebook based critical thinking skills offer solutions to facilitate learning critical thinking skills. The purpose of this research is to produce a viable ebook to facilitate learning critical thinking skills. This type of research is research and development using Dick, Carey, and Carey (2009) instructional design. The Research instruments use poll responses from experts, teachers and learners. The resulting development product is an ebook based on critical thinking skills. Based on the results of data analysis obtained from the responses of learning media experts, learning design experts, learning materials experts, individual trials, small group trials, and field trials showed that the developed ebooks could facilitate learning critical thinking skills with an average percentage of 88.67%. The outcome of the overall assessment of the test subject to critical thinking skills indicators has demonstrated validity and with an average percentage of 89.6% and can be interpreted that the teaching materials are developed worthy to facilitate Critical thinking skills.